Isotope values obtained along cores MD-1 and MD-3 in florida mangrove diebacks - Marcelo Cancela Lisboa Cohen (PANGAEA, 2024)
Samples (5–60 mg, 5 cm interval) were treated with 4% HCl to eliminate carbonate, washed with distilled water (pH 6), and dried at 50°C. Total organic carbon was determined at the Stable Isotope Laboratory of the Center for Nuclear Energy in Agriculture/University of São Paulo (CENA/USP). Results are presented in percentages of dry weight, with precision of 0.09% (Total Organic Carbon - TOC). The C/N data are presented as molar ratio. The organic matter δ13C values are presented as δ13Corg (VPDB standard) with precision of ±0.2 extperthousand.
In: Cohen, MCL (2024): Florida mangrove diebacks [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.964591